2019
DOI: 10.1111/pan.13612
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the relationship between postoperative nausea and vomiting and postdischarge nausea and vomiting in children undergoing ambulatory surgery

Abstract: Background:The factors contributing to postoperative nausea and vomiting in children have been identified, but there have been no reported studies that have studied pediatric postdischarge nausea and vomiting.Aims: This preliminary study aimed to identify the factors affecting postdischarge nausea and vomiting in ambulatory children, specifically whether postoperative nausea and vomiting factors are contributory. Methods:One hundred and twenty-two pediatric patients aged 5-10 years undergoing elective ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…For example, since patients must provide self-care after ambulatory surgery, it is possible that poor health literacy may be associated with adverse outcomes [ 15 , 16 ]. In addition, family support may also be a factor determining outcomes, especially for more vulnerable patients (e.g., seniors) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, since patients must provide self-care after ambulatory surgery, it is possible that poor health literacy may be associated with adverse outcomes [ 15 , 16 ]. In addition, family support may also be a factor determining outcomes, especially for more vulnerable patients (e.g., seniors) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Kocaturk et al . 40 , 41 found that when PONV persisted into the postdischarge period, pain was often a contributing factor. Turgut et al .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Alternative treatments for active PONV include intravenous metoclopramide (10 mg), droperidol (0.625 mg), promethazine (6.25–12.5 mg), dolasetron (12.5 mg), granisetron (0.1 mg), palonosetron (0.075mg), or tropisetron (0.5 mg) 419 , 420 . Algorithms describing how to identify high-risk patients and how to guide the administration of multimodal treatments can significantly reduce the incidence of PONV and PDNV 40 , 421 – 423 . Yazbeck-Karam et al .…”
Section: Combined Treatments For Managing Established Ponvmentioning
confidence: 99%
“…2,7,8 Despite these efforts, current interventions still lack universal efficacy. Chandrakantan et al 9 recently reported that neither ondansetron nor dexamethasone is proved effective in preventing nausea, either alone or in combination. In our hospital, PONV still occurs frequently despite a standard institutional guideline that includes routinely rehydration with 10 mL/kg IV fluid, and administration of ondansetron and dexamethasone in children above 2 years of age.…”
Section: Introductionmentioning
confidence: 99%